Contextos cerámicos y transformaciones urbanas en Carthago Nova : (s. II-III d.C.) - Quevedo, Alejandro, (Roman and late antique Mediterranean pottery ;, 2015)
The transition process of the Roman city between the Early Roman period and Late Antiquity is difficult to understand due to the absence of urban models and the decline in epigraphy. The transformations that accompany this period are detectable in the western provinces of the Empire from a very early time. Their interpretation varies with each study case. Ancient Cartagena is a paradigm of these changes. Starting under Marcus Aurelius, the city began to show symptoms of exhaustion, at the same time as literary and epigraphic evidence began to decline, until it disappeared altogether. In these pages the author contributes - and at the same time vindicates - an approach to discovering more about the 2nd and 3rd centuries AD based on the archaeological record and taking into account the stratigraphic sequences and especially the pottery material culture.